Eksistensi Asbabun Nuzul dan Tafsir Ilmi dalam Al-Qur’an - Nisfu Kurniyatillah; Mahmud Arif; Mohamad Syawaluddin (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2023)
The Qur'an was the handbook of Muslims to guide and direct the lives of Muslims throughout the world. In addition, the Al-Quran was also a basic reference or source in determining law in all aspects of life. Muslims were required to read, study, and practice the contents of the Qur'an. The existence of the Qur'an began to appear since the messenger of Allah Swt, namely Muhammad bin Abdullah Saw, received revelations sent through the angel Gabriel to inform orders, prohibitions, news, descriptions of unseen things and tell the previous people and determine the law for an incident that occurred. there at that time. The essence of studying the Koran was to understand deeply and in detail about the Koran, so the right effort for this was to understand asbabun nuzul. This study used a descriptive qualitative method with a focus on literature study. Thus, this study explained in detail about Nuzulul Qur'an, Sabab An-Nuzul and Tafsir Ilmi.